Challenges And Opportunities In The Development Of Halal Tourism In Indonesia - Marwah, Ahmad Hadirul; Rofiqo, Azidni (GERASI INSAN NUSANTARA, 2024)
This study seeks to identify and analyse the challenges and opportunities associated with the development of halal tourism in Indonesia, a strategic sector within an Islamic value-based tourism economy. Employing a descriptive qualitative approach, the research draws upon secondary data sourced from academic literature, industry reports, policy documents, and publications issued by relevant public institutions. The analysis adopts a content analysis method to trace patterns, dominant issues, and inter-actor relationships in the national development of halal tourism. Findings suggest that Indonesia possesses substantial potential to emerge as a leading halal tourism destination, owing to demographic advantages, cultural richness, and destination diversity. Nonetheless, several obstacles persist, including limited Muslim-friendly infrastructure, low halal literacy among industry stakeholders, and inadequate inter-agency coordination. These findings bear theoretical implications for strengthening halal tourism as a multidimensional construct, as well as managerial implications for policymakers and industry players in designing inclusive, sustainable, and adaptive development strategies responsive to the needs of global Muslim travellers. The study also opens pathways for future empirical investigations, including quantitative approaches or destination-specific case studies.